2014
DOI: 10.1111/jcmm.12227
|View full text |Cite
|
Sign up to set email alerts
|

The peripheral chimerism of bone marrow–derived stem cells after transplantation: regeneration of gastrointestinal tissues in lethally irradiated mice

Abstract: Bone marrow–derived cells represent a heterogeneous cell population containing haematopoietic stem and progenitor cells. These cells have been identified as potential candidates for use in cell therapy for the regeneration of damaged tissues caused by trauma, degenerative diseases, ischaemia and inflammation or cancer treatment. In our study, we examined a model using whole-body irradiation and the transplantation of bone marrow (BM) or haematopoietic stem cells (HSCs) to study the repair of haematopoiesis, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Trafficking and reconstitution of hematopoietic cell subsets following TBI is likely to be a generalized phenomenon that is independent of a given gene modification strategy (i.e., CD4CAR). This model is consistent with previous small animal studies from our group and others, demonstrating that donor HSC–derived cells traffic to lymphoid GCs ( 59 , 67 ), CNS tissues ( 61 , 68 71 ), and GIT ( 59 , 72 ). Lower-dose lymphodepleting chemotherapy regimens for CAR T cells are designed to activate cytokine expression in vivo to facilitate maintenance and expansion of the T cell compartment (including CAR T cells) ( 73 , 74 ).…”
Section: Discussionsupporting
confidence: 92%
“…Trafficking and reconstitution of hematopoietic cell subsets following TBI is likely to be a generalized phenomenon that is independent of a given gene modification strategy (i.e., CD4CAR). This model is consistent with previous small animal studies from our group and others, demonstrating that donor HSC–derived cells traffic to lymphoid GCs ( 59 , 67 ), CNS tissues ( 61 , 68 71 ), and GIT ( 59 , 72 ). Lower-dose lymphodepleting chemotherapy regimens for CAR T cells are designed to activate cytokine expression in vivo to facilitate maintenance and expansion of the T cell compartment (including CAR T cells) ( 73 , 74 ).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the levels of Sca1+/CXCR4+ BMDAC in the spleen are independent of donor age. By transplanting GFP + donor cells into GFP − recipient mice, Filip et al reported that N 40% of the recipient's own cells remained in the spleen after the bone marrow transplantation, while b 20% of the recipient's cells are found in the bone marrow and circulating blood [46]. The chimerism in the spleen may explain the similar levels of Sca1 +/CXCR4 + progenitor cells found in recipients with either young or old bone marrow.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, a preparation of acellular muscle grafts has been optimized (Gillies et al 2011), and their reseeding with myoblasts gave rise to engineered muscle constructs with histomorphological characteristics resembling native muscle which, under in vitro conditions, were capable of generating contractile force (Borschel et al 2004, Valentin et al 2010. Furthermore, we have demonstrated that high doses of whole-body irradiation also induce myeloablation and chimerism in tissues, and the entry of transplanted cells into the small intestine and liver (Filip et al 2014). However, other functional characteristics of these grafts reoccupied with myogenic and non-myogenic cells after implantation have yet to be determined in animal models.…”
Section: Skeletal Musclesmentioning
confidence: 96%
“…Thus, to understand the roles played by myogenic Ca 2+ signaling we must first consider: 1) the triggers and targets within these signaling domains; 2) interdomain signaling, and 3) how these Ca 2+ signals integrate with other signaling networks involved in myogenesis (Pubill et al 2001, Dayanithi et al 2012. Currently available imaging techniques that provide direct visualization and evaluation of these Ca 2+ signals have also been described (Dayamithi et al 2012, Forostyak et al 2013, including stem cells of various origins (Dayanithi and Verkhratsky 2016).…”
Section: Role Of Intracellular Ca 2+mentioning
confidence: 99%